Atypical gouty tophus masquerading as a foreign body granuloma - Farhana Omar; Abu Mansor Matardiah Nor Hashimah; Ab Wahab Suhaila; Farhana Mohammad Mohaidin; Azman Ali Raymond (SpringerOpen, 2024)
Abstract Subcutaneous nodular lesions in a patient with significantly elevated inflammatory markers always raise the possibility of infectious diagnoses such as atypical infection, pyogenic abscess, mycobacterial infection, and malignancy. Definitive diagnosis requires tissue biopsy and histopathologic examination. The atypical presentation of a foreign body granuloma with concurrent intraoperative findings supports the diagnosis of gouty arthritis. We report a case of a 67-year-old man who presented with an inflammatory nodular lesion on the left elbow that was initially suspected to have an infectious cause. Histopathologic examination of the nodular tissue later revealed that the patient had a foreign body granuloma due to urate crystal deposition. The atypical appearance of the gouty arthritis, the low serum urate level, the negative crystal identification in the synovial fluid, and the markedly elevated inflammatory markers, which did not respond to the previous antibiotic and steroid therapy, raised the suspicion of atypical infection in this case.